Presentation, Treatment, and Outcomes of Older Adults Hospitalized for Acute Myocardial Infarction According to Cognitive Status: The SILVER-AMI Study - Hajduk, Alexandra M; Saczynski, Jane S; Tsang, Sui; Geda, Mary E; Dodson, John A; Ouellet, Gregory M; Goldberg, Robert J; Chaudhry, Sarwat I (The American journal of medicine, 2021)
While survival after acute myocardial infarction has improved substantially, older adults remain at heightened risk for hospital readmissions and death. Evidence for the role of cognitive impairment in older myocardial infarction survivors' risk for these outcomes is limited. 3041 patients aged ≥75 years hospitalized with acute myocardial infarction (mean age 82 ± 5 years, 56% male) recruited from 94 US hospitals. Cognition was assessed using the Telephone Interview for Cognitive Status; scores of <27 and <22 indicated mild and moderate/severe impairment, respectively. Readmissions and death at 6 months post-discharge were ascertained via participant report and medical record review. Associations between cognition and outcomes were evaluated with multivariable-adjusted logistic regression. Mild and moderate/severe cognitive impairment were present in 11% and 6% of the cohort, respectively. Readmission and death at 6 months occurred in 41% and 9% of participants, respectively. Mild and moderate/severe cognitive impairment were associated with increased risk of readmission (odds ratio [OR] 1.36; 95% confidence interval [CI], 1.08-1.72 and OR 1.58; 95% CI, 1.18-2.12, respectively) and death (OR 2.19; 95% CI, 1.54-3.11 and OR 3.82; 95% CI, 2.63-5.56, respectively) in unadjusted analyses. Significant associations between moderate/severe cognitive impairment and death (OR 1.69; 95% CI, 1.10-2.59) persisted after adjustment for demographics, myocardial infarction characteristics, comorbidity burden, functional status, and depression, but not for readmissions. Moderate-to-severe cognitive impairment is associated with heightened risk of death in older acute myocardial infarction patients in the months after hospitalization, but not with readmission. Routine cognitive screening may identify older myocardial infarction survivors at risk for poor outcomes who may benefit from closer oversight and support in the post-discharge period.